2022
DOI: 10.3389/fpls.2022.772621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity on a Rare Terrestrial Orchid, Habenaria linearifolia in South Korea: Implications for Conservation Offered by Genome-Wide Single Nucleotide Polymorphisms

Abstract: Monitoring intraspecific diversity offers invaluable insights on conservation practices as the variation is the product of species evolution. Accordingly, the role of population genetic diversity has drawn great attention over the last century responding to the biodiversity loss induced by a series of anthropogenic changes. Orchids are one of the most diverse, yet ironically most rapidly disappearing plant groups due to the specialized habitat preferences. Thus, population-level genetic diversity studies may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Likewise, the threatened Cypripedium japonicum [37], Laelia rubescens [38], Laelia speciosa [39], Brassavola nodosa [40] or Neofinetia falcata [41] species also show low genetic diversity values [42]. Epiphytic orchids studied here also show low patterns of genetic diversity, namely M. rosea (Table 1).…”
Section: Population Genetic Diversitymentioning
confidence: 67%
“…Likewise, the threatened Cypripedium japonicum [37], Laelia rubescens [38], Laelia speciosa [39], Brassavola nodosa [40] or Neofinetia falcata [41] species also show low genetic diversity values [42]. Epiphytic orchids studied here also show low patterns of genetic diversity, namely M. rosea (Table 1).…”
Section: Population Genetic Diversitymentioning
confidence: 67%
“…The denser the vegetation, the shorter the seed propagation distance, and the more limited the gene exchange between populations [ 41 ]. For instance, Lee et al [ 42 ] studied Habenaria linearifolia and found that it is mainly located on a plateau that is surrounded by dense tall grasses. This growth environment limits seed dispersal and thus hinders gene exchange.…”
Section: Discussionmentioning
confidence: 99%